2018
DOI: 10.1016/j.scitotenv.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Gas-fired power in the UK: Bridging supply gaps and implications of domestic shale gas exploitation for UK climate change targets

Abstract: There is a projected shortcoming in the fourth carbon budget of 7.5%. This shortfall may be increased if the UK pursues a domestic shale gas industry to offset projected decreases in traditional gas supply. Here we estimate that, if the project domestic gas supply gap for power generation were to be met by UK shale gas with low fugitive emissions (0.08%), an additional 20.4MtCOe would need to be accommodated during carbon budget periods 3-6. We find that a modest fugitive emissions rate (1%) for UK shale gas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…In addition, there may have been another reason for the increase in proportion of gas production. Some studies have shown that the reason for an increase in global gas dependency on energy use has been due to environmental concerns and the production of shale oil and gas [25].…”
Section: Discussion Of Technological Development Changes In Market Ementioning
confidence: 99%
“…In addition, there may have been another reason for the increase in proportion of gas production. Some studies have shown that the reason for an increase in global gas dependency on energy use has been due to environmental concerns and the production of shale oil and gas [25].…”
Section: Discussion Of Technological Development Changes In Market Ementioning
confidence: 99%
“…At present, the feasibility of establishing a national hydrogen economy partially based on SMR + CCS [180,188] is constrained by the progressive depletion of domestic gas reserves in the UK Continental Shelf (UKCS) [189], as reflected by the country's status as a net importer of energy since 2004 [190]. Increased natural gas imports would be needed to address this supply gap [190,191]. Alongside these challenges, fuel conversion inefficiencies need to be addressed for blue hydrogen production [176].…”
Section: Barriers To a Blue Hydrogen Pathway Fuel Costs Represent The...mentioning
confidence: 99%
“…This bias can even extend to the LCA itself, as exemplified by ExxonMobil (Kennelly et al, 2019). This trend becomes more prominent in certain industries where regulators incentivise the adoption of consumption-based carbon accounting, leading to the preference for importing natural gas rather than producing it domestically (Turk et al, 2018) (2015) found this to be the case with a biogas facility. Therefore, it is crucial to adopt a consistent, standardised and transparent approach to facilitate the wider application of PB LCA models beyond local and sub-local levels.…”
Section: Company-level Data and Modelsmentioning
confidence: 99%